Autoimmune Pancreatitis - A Case Report - Varuna Mallya (Journal of Clinical and Diagnostic Research, 2015)
Autoiommune pancreatitis (AIP) is a rare disease that has distinct histological, immunological, serological and radiological findings. It is characterised histologically by lymphoplasmacytic infiltrate, storiform fibrosis, obliterative phelibitis and presence of IgG4 positive plasma cells and lymphocytes. Elevated serum levels of IgG4 are also noted. It is usually misdiagnosed preoperatively as pancreatic cancer. It may involve extrapancreatic sites also and responds well to steroid therapy. Here, we share our experience of AIP in a 52-year-old male.